Participatory validation of the ethno-veterinary practices followed by the livestock farmers in the vicinity of Ranthambore Tiger Reserve, India (Indian Journal of Traditional Knowledge (IJTK), 2024)
The livestock farmers in the vicinity of Ranthambore Tiger Reserve (RTR) have a large knowledge of indigenous knowledge regarding the use of various plant species, herbs, shrubs, homemade ingredients, etc., for the treatment of various health problems in the livestock. The current study was aimed at documenting and evaluating the traditional veterinary practices used by livestock owners to treat common health issues in animals, such as retained placenta, blood in urine, skin conditions, and constipation. The research was conducted in a specifically chosen area, namely the Critical Tiger Habitat and buffer of the tiger reserve and a 360 livestock farmers were interviewed from the 30 villages in the vicinity of the Ranthambore Tiger Reserve. An open-ended interview schedule was used to record ethno-veterinary practices. To facilitate participatory evaluation of the identified practices, the Quantification of Indigenous Knowledge (QuIK) method was employed. To treat four common health ailments, the farmers used 15 ethno-veterinary methods. Uses of Triticum aestivum to treat retained placenta, roots of Urtica dioica L. against the haematuria, paste of Azadirachta indica for skin disease, and roots of Citrullus colocynthis L. for treatment of constipation in the livestock were found most effective practices. Hence, before further replication and application, the pharmacodynamics of these ethno-veterinary practices could be investigated.